2023
DOI: 10.3389/fendo.2023.1061704
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and metabolic characters of KCNJ5 somatic mutations in primary aldosteronism

Abstract: BackgroundPrimary aldosteronism (PA) is the leading cause of curable endocrine hypertension, which is associated with a higher risk of cardiovascular and metabolic insults compared to essential hypertension. Aldosterone-producing adenoma (APA) is a major cause of PA, which can be treated with adrenalectomy. Somatic mutations are the main pathogenesis of aldosterone overproduction in APA, of which KCNJ5 somatic mutations are most common, especially in Asian countries. This article aimed to review the literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 137 publications
(161 reference statements)
0
2
0
Order By: Relevance
“…KCNJ5 is a Potassium Inwardly Rectifying Channel Subfamily J Member 5, which encodes a G-protein-activated inward rectifier potassium channel. [17] This potassium channel mediates the outward current of potassium ions to maintain hyperpolarization and stabilize the resting membrane potential. [18] To date, most studies have focused on the relationship between the KCNJ5 mutation and aldosteronism caused by adrenal adenoma, [19] and it has been found that overexpression of KCNJ5 can inhibit the growth of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…KCNJ5 is a Potassium Inwardly Rectifying Channel Subfamily J Member 5, which encodes a G-protein-activated inward rectifier potassium channel. [17] This potassium channel mediates the outward current of potassium ions to maintain hyperpolarization and stabilize the resting membrane potential. [18] To date, most studies have focused on the relationship between the KCNJ5 mutation and aldosteronism caused by adrenal adenoma, [19] and it has been found that overexpression of KCNJ5 can inhibit the growth of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…2 The authors stressed the primary aldosteronism in a transient hypertension of pregnancy. Chang YY et al reviewed clinical data and genetic mutations among patients with PA. 3 They cited PA as now considered the most common modifiable secondary hypertension (up to 15%), and up to 30% of the resistant and refractory cases; while aldosteronoma (30%-35%) and bilateral adrenal hyperplasia (60%-65%) are the major causes of PA. 3 Besides, the patients with KCNJ5 somatic mutations can have higher left ventricle mass (LVM), inappropriately excessive LVM, and better improvement after adrenalectomy. 3 Jia M et al reported 3 patients with biochemically confirmed PA, and the diagnoses were delayed by aldosterone-to-renin ratio (ARR) initial analysis with non-suppressed renin.…”
Section: Dear Editormentioning
confidence: 99%
“…Chang YY et al reviewed clinical data and genetic mutations among patients with PA. 3 They cited PA as now considered the most common modifiable secondary hypertension (up to 15%), and up to 30% of the resistant and refractory cases; while aldosteronoma (30%-35%) and bilateral adrenal hyperplasia (60%-65%) are the major causes of PA. 3 Besides, the patients with KCNJ5 somatic mutations can have higher left ventricle mass (LVM), inappropriately excessive LVM, and better improvement after adrenalectomy. 3 Jia M et al reported 3 patients with biochemically confirmed PA, and the diagnoses were delayed by aldosterone-to-renin ratio (ARR) initial analysis with non-suppressed renin. 4 The reevaluated ARR was close to cutoff still with normal renin after strict and extended drug washout, and a further workup for PA showed a unilateral aldosterone producing adenoma that was surgically removed, with subsequent complete biochemical remission.…”
Section: Dear Editormentioning
confidence: 99%
“…Over the past two decades, numerous studies have explored primary hyperaldosteronism, 21 with recent advancements in genetic research, 22 , 23 diagnostic testings, 24 26 and prognostic factor evaluations, 11 , 22 which have deepened our understanding of the disease. However, despite these advancements, there remained a notable gap in the literature regarding the comparative efficacy of different medical treatments.…”
Section: Introductionmentioning
confidence: 99%